Can paediatric emergency clinicians identify and manage clavicle fractures without radiographs in the emergency department? A prospective study - Marie-Pier Lirette; Benoit Bailey; Samuel Grant; Michael Jackson; Paul Leonard (BMJ Publishing Group, 2018)
Background Paediatric clavicle fractures are commonly seen in the emergency department (ED), and the current standard of care is to obtain a radiograph for all suspected clavicle fractures. We are yet to determine whether radiographs add valuable information to clinicians' assessment and therefore if they are necessary in the management of paediatric clavicle fractures.Objective To determine whether clinicians can manage paediatric clavicle fractures without radiographs, first by determining the accuracy of clinicians in identifying the presence of a clavicle fracture, and second by evaluating the level of agreement (kappa (κ)) between the ultimate management of children with suspected clavicle fractures and clinicians' blinded prediction prior to the radiograph.Methods This prospective study enrolled patients presenting to a paediatric ED with a suspected clavicle fracture. Prior to requesting a radiograph, clinicians completed a standardised form, where they predicted the presence of a fracture and their ultimate management based on their clinical findings, and rated their confidence.Results Of the 50 patients aged 7.2±3.9 years included, 40 (80%) had a radiologically proven clavicle fracture, and clinicians were able to accurately identify them (sensitivity 93%, positive predictive value 88%). There were five (50%) patients without a radiological fracture that were treated with broad arm sling. Clinicians' prediction of ultimate management had the highest agreement with the ultimate management of the patient on leaving the ED, compared with clinicians' prediction of the presence of fracture and the final radiograph findings: κ of 0.88 (95% CI 0.64 to 1), 0.67 (95% CI 0.36 to 0.98) and 0.62 (95% CI 0.30 to 0.94), respectively. Thirty-six (72%) of the clinicians felt comfortable treating without radiographs, and this was dependent on their level of training.Conclusions Clinicians can identify the presence of a fracture and tend to be overconservative in their management. Despite negative radiological findings, some patients were treated as though they had a fracture, based on clinical judgement. This adds evidence that radiographs are not routinely required for uncomplicated paediatric clavicle fractures.